2005
DOI: 10.1086/430928
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of DB289 in Thai Patients withPlasmodium vivaxor Acute, UncomplicatedPlasmodiumfalciparumInfections

Abstract: DB289 is a promising new antimalarial compound that could become an important component of new antimalarial combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…In clinical trials involving patients with primary stage African trypanosomiasis, treatment with oral DB289 (100 mg, twice daily for 10 days) achieved cure rates of approximately 95% (Dr. Carol Olson, Immtech Pharmaceuticals Inc., personal communication). In clinical trials involving patients with Plasmodium vivax or acute, uncomplicated P. falciparum, treatment with oral DB289 (100 mg, twice daily for 5 days) achieved cure rates of 96% (Yeramian et al, 2005). Oral DB289 was also well tolerated, with no serious side effects (Yeates, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials involving patients with primary stage African trypanosomiasis, treatment with oral DB289 (100 mg, twice daily for 10 days) achieved cure rates of approximately 95% (Dr. Carol Olson, Immtech Pharmaceuticals Inc., personal communication). In clinical trials involving patients with Plasmodium vivax or acute, uncomplicated P. falciparum, treatment with oral DB289 (100 mg, twice daily for 5 days) achieved cure rates of 96% (Yeramian et al, 2005). Oral DB289 was also well tolerated, with no serious side effects (Yeates, 2003).…”
mentioning
confidence: 99%
“…Clinical trials in humans demonstrated oral DB289 to be well absorbed and efficiently converted to DB75. However, pharmacokinetic studies have indicated that DB75 plasma concentrations are highly variable among patients (Yeramian et al, 2005). Such variability could be due in part to interindividual differences in the extent of metabolic conversion of DB289 to DB75.…”
mentioning
confidence: 99%
“…DB289 30 has originally been developed for the treatment of the first stage of African sleeping sickness. In a small (23 patients) Phase-II clinical trial against P. vivax and uncomplicated P. falciparum infections, pafuramidine 30 demonstrated 96% efficiency and good tolerability [172].…”
Section: Pafuramidine (Db289)mentioning
confidence: 99%
“…1), an orally bioavailable prodrug of furamidine II (Fig. 1), is currently in phase III trials for pneumocystis pneumonia and HAT [1, [3][4][5][6][7]. It has been suggested that DNA minor groove binding at AT rich sites is essential for the antimicrobial activity of dications [1].…”
Section: Introductionmentioning
confidence: 99%